Multiphase flow model and experimental study of pressure swing distillation for low pressure process of hydrochloric/water separation in hydrogen production. (4th October 2020) - Farsi, Aida; Kayhan, Öznur; Chehade, Ghassan; Dincer, Ibrahim; Natarer, Greg F.
Highlights: An experiment study for the HCl/water binary mixture through PSDU is proposed. A dynamic model is developed to study the batch distillation process. The column temperature profile and products molar concentrations are established. The experimental results are compared with the simulation results. Abstract: Extraction of water from a concentrated HCl(aq) azeotropic solution is one of the challenging processes in recycling of anolyte within the copper-chlorine (Cu-Cl) cycle of hydrogen production. To pass the azeotropic point, a distillation process needs to take place in high pressure and low pressure columns. In this paper, a new lab-scale pressure swing distillation unit (PSDU) is developed and presented. The low pressure side of the PSDU is operated as a batch process to separate HCl(aq). A dynamic model for this process is formulated. Currently there is a lack of experimental data for this process so this study presents new measured data for the separation of HCl(aq). During the experiment, the temperature and concentration profiles are recorded as a bench-mark for reference in further next studies. The predictive model is verified with experimental results. The results of the experiments and simulations are provided, compared and discussed. The simulation results show reasonable agreement with the experimental data.